Biodegradation of Azo Dyes in Synthetic Medium and Textile Effluent using a Potent Bacterium Bacillus sp. TDS50 and its Extracellular Metabolites - Mutharasu, Divya; Sundaram, Rajakumar; Munusamy, Ayyasamy Pudukkadu (Asian Journal of Chemistry, 2025)
Azo dyes in textile effluents, pose substantial environmental problems owing to their persistence, toxicity and potential to form harmful carcinogenic and mutagenic byproducts, like aromatic amines. This study aimed to evaluate the degradation of reactive red (RR) and reactive blue (RB) azo dyes by an indigenous bacterial strain (Bacillus sp. TDS50) isolated from textile industry effluent. The Bacillus sp. TDS50, showed the highest decolorization efficiency of 98.30% for RR and 98.02% for RB. The strain showed its significant decolorization of azo dyes using glucose as a carbon source, pH 7, temperature 35 ºC, dye concentration 100 mg/L and an inoculum size 1%. A laboratory scale bioreactor was used to decolourize the dyes under optimum conditions. An analytical study of the degraded product was performed using FTIR spectroscopy and gas chromatography-mass spectroscopy (GC-MS). Another major focus of this investigation was decolourization in an aqueous medium using bacterially produced extracellular metabolites, viz. bioflocculants (BF) and biosurfactants (BS). The results of the bacterial treatment followed by phytotoxicity indicated the non-toxic nature of the treated effluent compared to untreated effluents.